THE INFLUENCE OF INSTAGRAM DA’WAH ACCOUNT ON RELIGIOUS BEHAVIOR - Andini Nur Bahri (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2020)
Abstract Instagram is a popular social media recently and most of its users are young people including students. Students are interested in using Instagram because it has interesting features such as photos and videos that can add to their insight, this also includes Islamic teachings. Many students become followers of the da’wah accounts that th ey access every day. This study aims to determine the influence of da’wah Instagram accounts on religious behavior among students of Islamic Communication and Broadcasting at the Islamic State University of North Sumatra. The research method used is a quantitative method. The result shows that there is no significant effect of the da’wah Instagram accounts on religious behavior